Application of a circulating-cathodic-antigen (CCA) strip test and real-time PCR, in comparison with microscopy, for the detection of Schistosoma haematobium in urine samples from Ghana - Obeng, B.B.; Aryeetey, Y.A.; de Dood, C.J.; Amoah, A.S.; Larbi, I.A.; Deelder, A.M.; Yazdanbakhsh, M.; Hartgers, F.C.; Boakye, D.A.; Verweij, J.J.; van Dam, G.J.; van Lieshout, L. (Annals Tropical of Medicine and Parasitology 102(7): 625-33, 2008)
In the detection of parasitic infection, the traditional methods based on microscopy often have low sensitivity and/or specificity compared with the newer, molecular tests. An assay based on real-time PCR and a reagent strip test for detecting circulating cathodic antigen (CCA) have both now been compared with urine filtration and microscopy, in the detection of Schistosoma haematobium infections. Urine samples, obtained from 74 'cases' in areas of Ghana with endemic S. haematobium and 79 'controls' from non-endemic areas, were each checked using the three methods. With the results of the filtration and microscopy taken as the 'gold standard', real-time PCR was found to be 100% specific and 89% sensitive whereas the CCA strips were 91% specific and 41% sensitive. With the samples found to contain > or =50 eggs/10 ml (indicating relatively intense infections), the sensitivities of the PCR and CCA were higher, at 100% and 62%, respectively. As expected, egg counts were negatively correlated with the number of amplification cycles needed, in the PCR, to give a signal that exceeded the background (r=-0.38; P<0.01). Although the real-time PCR and CCA strip tests are very different, both show promise in the detection of S. haematobium infections. The PCR has optimal specificity and high sensitivity but the specificity of the CCA strips and the sensitivity of both tools could still be improved. A more thorough re-evaluation of the sensitivity and specificity of microscopy and these newer diagnostic methods, with an estimation of the cost-effectiveness of each technique, is recommended.